Effectiveness of Vestibular Stimulation on Visual Motor Integration Among Children with Learning Disabilities - DR. SILPA IMMANUEL.V,; BAKARA BARAKAT,; DR.PRINCE.K,; R.THILAGAVATHI, (International Journal of Pharma and Bio Sciences, 2018)
Learning disability (LD) has received significant attention recently in the light of the urgent need to identify and remediate in order to minimize and prevent its disabling effects on learning in individuals. This study was done to find out the effects of vestibular stimulation on Visual Motor Integration (VMI) among LD children. Quasi experimental research design and convenience sampling procedure was done for the study. Fourteen participants within the age range of 7-12 years were selected and equally divided into two groups. The Beery VMI and Sensory Profile (vestibular processing) were the outcome measures. The experimental group was given Vestibular stimulation along with SI and Control group was given only SI, thrice a week for 8 weeks. Non parametric tests Wilcoxon Signed Rank test at 5 % level of significance was used to find out the difference in pre- and post-test means within the group and Mann Whitney U test at 5 % level of significance was used to compare the effect of Vestibular stimulation between the experimental and control group. The results revealed p<0.05 only with VMI test and not with supplementary tests. Therefore, Vestibular stimulation through jumping, sliding, and swinging are effective in improving Visual Motor Integration and vestibular stimulation could be used as an adjuvant in Occupational therapy.